Well-boring for water, brine and oil a manual of current practice - Isler, C. (E. & F.N. Spon, 1902)
While water is the fluid most often sought by boring, precisely similar methods are applied to other liquid minerals, such as brine and petroleum, and most of the matter contained in these pages may be regarded as referring to all of them.